Accessing and utilizing services by rural borderland communities in South-Western Nigeria - Kehinde O. Popoola; Susanne E. Speak (Economic and Environmental Studies (E&ES), 2019)
Borderland communities hold a strategic position in many countries. However, in spite of this, many of these communities, specifically in Nigeria, are still characterized by neglect and underdevelopment. Based on the above fact, this study explores the service deprivation and coping strategies of rural borderland communities in South-Western Nigeria. The study revealed that the majority of inhabitants of rural borderland (64.0%) get their water supply straight from streams and are bound to cover distances of 500 meters or longer to collect water. Similarly, the majority of them defecate in bush reserves around their houses. Also, the study showed that people can travel across the national border to neighboring countries on a regular basis to access basic services, like healthcare facilities. Likewise, medical personnel or attendants from neighboring countries or towns are called during critical or serious illness to render services which the Nigerian Government does not provide. The development of Nigeria's frontier areas is therefore of paramount importance and really pending, and must be made priority in urgent and major developmental actions taken in the country.
Keywords: I31; D63; 330; access to services; rural communities; borderland communities; deprivation; South-Western Nigeria